News media bargaining codes - Luca Sandrini; Robert Somogyi (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We build a model of the news market where advertisers allocate their ads between a social media platform and a news website. Our objective is to evaluate policy interventions aimed at fostering news creation by transferring revenues from social media to news websites already introduced in Australia, Canada, and Indonesia). We show that social media may voluntarily contribute to news development, but only suboptimally. Beyond a certain level of state-mandated transfer, the social media platform can credibly threaten to remove news content. We provide some guidance on how to design a policy that improves welfare by promoting news creation.
Keywords: D43; D62; L13; L51; M37; 330; social media; news quality; platform regulation; news media bargaining code; online advertising